Broadcasting Policy in Canada - ROBERT ARMSTRONG (University of Toronto Press, 2010)
This book examines government policies related to broadcasting in Canada and the strategies in place to safeguard and strengthen the Canadian broadcasting system. The discussion also addresses related issues such as television and radio production financing, copyright, the Internet, social concerns, and cultural diversity in a global media environment. Broadcasting is the only regulated cultural medium in Canada. The material presented here provides an introduction to broadcasting regulation, the history of broadcasting legislation and policy, and the origins and objectives of relevant government policies. The discussion is conducted with particular attention to broadcasting policy development and, while issues of political power are addressed, power relationships are not the primary focus of the book. The Canadian broadcasting system is constantly changing and any attempt to summarize or analyse Canadian broadcasting policy at one point in time is certain to be overcome by subsequent events. This book is current to July 2009, but since broadcasting policy continues to evolve, the reader is encouraged to supplement his or her knowledge by monitoring developments in the daily press and at the Internet websites of the major Canadian broadcasting policymakers mentioned herein. All of the Canadian Radio-television and Telecommunications Commission’s decisions and notices contained in this book are available on its website at http://www.crtc.gc.ca.